The effects of extreme weather conditions on Hong Kong and Shenzhen stock market returns - Zhuhua Jiang; Sang Hoon Kang; Chongcheul Cheong; Seong-min Yoon (International Journal of Financial Studies, 2019)
We investigate the impact of extreme weather conditions on the stock market returns of the Hong Kong Stock Exchange and Shenzhen Exchange. For the weather conditions, we apply dummy variables generated by applying a moving average and moving standard deviation. Our study provides two interesting results. First, extreme weather conditions have a significant impact on the stock returns of the Shenzhen Exchange, indicating that the Shenzhen market is inefficient. Second, during the pre-QFII period, extreme weather conditions have a strong impact on the returns of the Shenzhen stock market, but the impact is significantly weaker in the period after QFII. This means that the efficiency of the Shenzhen stock market has significantly increased since the QFII program due to the market openness to foreign institutional investors. We emphasize the role of foreign investors not affected by local weather conditions by observing how market opening affects extreme weather impacts on stock market returns.
Keywords: C32; F36; G11; G14; 330; behavioral finance; extreme weather; financial market openness; investment sentiment; MA-MSD method; QFII plan